The Role of IgA in Chronic Upper Airway Disease: Friend or Foe? - Sánchez Montalvo, Alba; Gohy, Sophie; Rombaux, Philippe; Pilette, Charles; Hox, Valérie (Frontiers in Allergy, 2022)
Chronic upper airway inflammation is amongst the most prevalent chronic disease entities in the Western world with prevalence around 30% (rhinitis) and 11% (rhinosinusitis). Chronic rhinitis and rhinosinusitis may severely impair the quality of life, leading to a significant socio-economic burden. It becomes more and more clear that the respiratory mucosa which forms a physiological as well as chemical barrier for inhaled particles, plays a key role in maintaining homeostasis and driving disease. In a healthy state, the mucosal immune system provides protection against pathogens as well as maintains a tolerance toward non-harmful commensal microbes and benign environmental substances such as allergens. One of the most important players of the mucosal immune system is immunoglobulin (Ig) A, which is well-studied in gut research where it has emerged as a key factor in creating tolerance to potential food allergens and maintaining a healthy microbiome. Although, it is very likely that IgA plays a similar role at the level of the respiratory epithelium, very little research has been performed on the role of this protein in the airways, especially in chronic upper airway diseases. This review summarizes what is known about IgA in upper airway homeostasis, as well as in rhinitis and rhinosinusitis, including current and possible new treatments that may interfere with the IgA system. By doing so, we identify unmet needs in exploring the different roles of IgA in the upper airways required to find new biomarkers or therapeutic options for treating chronic rhinitis and rhinosinusitis.